SERTIFIKASI DA'I DALAM LENSA LITERASI PUBLIK: ANALISIS KRITIS PODCAST 'HOTROOM' - Aly, Abdul Hamid; Mimin Aminah (KOHESI : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
This study analyzes the discourse on da'i (Islamic preacher) certification through the lens of public literacy by critically examining the Hotroom podcast. The certification of da'i has become a significant discourse in Indonesia, aiming to enhance the professionalism of Islamic preaching, moderate religious teachings, and curb the spread of radicalism. However, the policy has sparked controversy concerning the freedom of religious expression and the plurality of Islam. The Hotroom podcast, as a digital medium, serves as an interactive forum that brings together diverse perspectives from legislators, religious scholars, and the public. Using a qualitative descriptive approach and critical discourse analysis, this study investigates the narratives, rhetoric, and ideologies embedded in the discussions around da'i certification. The findings reveal two dominant narratives: a positive narrative that supports certification as a step toward the professionalization of dakwah (Islamic preaching), and a critical narrative that rejects the policy on the grounds that it restricts freedom of speech. Community-based alternatives, such as non-formal training and standardization, are proposed to maintain inclusivity and local relevance. The analysis highlights the importance of collaboration between the government, religious organizations, and civil society in designing adaptive and tolerant religious policies. As a medium of public literacy, the podcast proves effective in presenting complex issues reflectively, fostering democratic dialogue, and promoting critical public awareness. This research contributes to the development of humanistic and adaptable religious policymaking in the digital age.